Images of Polish politicians on Facebook and Twitter on the example in communication strategies of Andrzej Duda and Donald Tusk - Adamik-Szysiak, Małgorzata (Polityka i Społeczeństwo, 2024)
The main purpose of shaping a specific political image is usually political pragmatism focused on gaining social and electoral support. Social media due to their specificity are an excellent space that allows politicians to self-present. The aim of the research is an attempt to construct a proposition of types of political images created in social media based on the analysis of communication strategies (including the tools used and persuasion techniques) of the two selected leading Polish politicians: Andrzej Duda and Donald Tusk. Particular attention is paid to the means of self-presentation, including the role of visual rhetoric in messages politicians on their official Facebook and Twitter accounts.